Peri-estrus ovarian, uterine, and hormonal variables determine the uterine luminal fluid metabolome in beef heifers - Silva, Felipe A C C; da Silva, Gabriela F.; Vieira, Bruna S.; Neto, Adomar L.; Rocha, Cecilia C.; Lo Turco, Edson G.; Nogueira, Guilherme P. [UNESP]; Pugliesi, Guilherme; Binelli, Mario (Oxford University Press (OUP), 2021)
In cattle, uterine luminal fluid (ULF) is the main source of molecules that support embryo development and survival during the peri-implantation period. Our overarching hypothesis is that peri-estrus changes in uterine function, including ULF accumulation and absorption, are uneven among individuals, and affect ULF composition and fertility. Our objectives were (1) to characterize temporal and spatial changes in ULF volume, endometrial and luteal blood perfusion, endometrial and luteal size, and circulating progesterone concentrations during the peri-estrus period in beef heifers and (2) to associate such changes with the metabolite composition in the ULF, 4 days after estrus (d 0). Fourteen Bos indicus heifer that presented a PGF2α responsive CL received 500 μg PGF2α analog i.m. and were examined daily by rectal B-mode and pulse-wave color-Doppler ultrasonography until the fifth day after estrus (d 5). The composition of the ULF was analyzed by targeted mass spectrometry on d 4. Multivariate analyses clustered heifers according to ovarian, uterine, and hormonal variables in clusters A (n = 5) and B (n = 8 heifers). Concentrations of Pro, Ala, Leu, Gly, Val, Lys, Ile, Phe, Asp, Orn, Tyr, Arg, Trp, Suc, Cit, ADMA, the sum of essential Amino Acids (AA), sum of nonessential AA, sum of aromatic AA, and total AA were greater in cluster A (FDR ≤ 0.05). ULF volume dynamics and uterine, ovarian, and hormonal variables during the peri-estrus period presented a concerted variation among heifers within clusters, which was associated with the ULF composition 4 days after estrus.
Keywords: beef heifers; peri-estrus period; uterine luminal fluid metabolome